A conservation framework for the historic interior scheme of heritage museum building in peninsular Malaysia / Norashikin Abdul Karim - Abdul Karim, Norashikin (2020)
Heritage museum buildings have seen rapid growth in the past few decades in Peninsular Malaysia. They constitute important national heritage asset requiring preservation. This heritage assets, both their exterior and interior, have their own historical significance. The buildings carry a uniqueness with regard to the historic interior scheme (HIS) as each of the building is filled with different interior features, room function, spatial design, variety of historic material, finishes, and even the associated historic events. Unfortunately, the significance of the historic interior scheme significances have disappeared due to the exhibitions in the museums. Accordingly, the historic integrity in preserving the heritage museum buildings cannot be complied with and even the significance of the HIS is not highlighted in the exhibition. Such contradiction caused the exhibition scheme to conflict with the original scheme of the museum building. These issues clearly strengthen that the two theories, historic integrity and historic interpretation, are the main focus of the study hence the knowledge gap. The aims of this research is to propose a conservation framework for preserving the HIS of a heritage museum building. The proposed framework aims to improve the historic scheme of the heritage museum buildings in Peninsular Malaysia. The focus of this study is to fulfill the two objectives, i.e. to authenticate the level of change (LoC) on the HIS that influences the authenticity of a heritage building conservation and to verify the degree of acceptance (DoC) of the heritage exhibition interpretation practice according to the heritage building museum standards of the historic interior scheme. This research is a qualitative research that adopts the case study method. The following heritage museum buildings were selected as case studies: the Penang Malay Gallery, George Town Penang; the National Education Museum, UPSI, Tanjung Malim Perak; the History and Ethnography Museum, Malacca; and the Kelantan Royal Custom and Tradition Museum, Kelantan. These four case studies are chosen because they are gazetted by the National Heritage Department Malaysia and have been certified as historical sites by the Ministry of Tourism, Arts and Culture Malaysia. The evaluation approach is used by using the evaluation form to obtain the data. There is two evaluation that involved in this research; Historic Interior Scheme (HIS) Evaluation and Heritage Exhibition Scheme (HES) Evaluation. This evaluation was carried out with the support of on-site observation, measured drawings, documents study, site tour, and reference to curators and museum experts. A photographic mapping technique was adopted using historic photograph, sketches, drawings, books, and journals to investigate the origin of the museum’s interior space. The data were analyzed and presented with color-coding in a table form to differentiate the pattern of the findings. The results indicated that the conservation framework for the HIS of the heritage museum buildings is important for acquiring the appropriate HIS with the right historic interpretation.